2014
DOI: 10.3846/16111699.2012.720587
|View full text |Cite
|
Sign up to set email alerts
|

Trade Openness and Economic Growth: Empirical Evidence From India

Abstract: The main objective of this study is to develop first time trade openness index and use this index to examine the link between trade openness and economic growth in case of India. This study employs a new endogenous growth model for theoretical support, auto-regressive distributive lag model and rolling window regression method in order to determine long run and short run association between trade openness and economic growth. Further granger causality test is used to determine the long run and short run causal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
70
3
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(110 citation statements)
references
References 31 publications
11
70
3
5
Order By: Relevance
“…movement and removal of trade barriers within region. The latest studies also support the argument that trade liberalization is negatively linked with the economic growth of a country (Rodriguez & Rodrik, 2000;Adhikary, 2011;Hye, Lau, 2015) especially low income countries (Sakyi, Villaverde & Maza, 2015). The studies in which the positive relationships between open trade policies have positive impact on economic growth indicated that in those case key beneficiaries of such policies are rich countries (Kim, Lin & Suen, 2011).…”
Section: Journal Of Management and Research Volume 3 Number 2 2016mentioning
confidence: 72%
“…movement and removal of trade barriers within region. The latest studies also support the argument that trade liberalization is negatively linked with the economic growth of a country (Rodriguez & Rodrik, 2000;Adhikary, 2011;Hye, Lau, 2015) especially low income countries (Sakyi, Villaverde & Maza, 2015). The studies in which the positive relationships between open trade policies have positive impact on economic growth indicated that in those case key beneficiaries of such policies are rich countries (Kim, Lin & Suen, 2011).…”
Section: Journal Of Management and Research Volume 3 Number 2 2016mentioning
confidence: 72%
“…The relationship between international trade and economic growth is one of the major concerns in academic researches (Singh, 2010). Hye and Lau (2015) identified the close linkage between trade and economic growth. Baldwin and Robert-Nicoud (2008) addressed international trade and economic growth with heterogeneous firms.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Healy and Wahlen (1999) draw attention to popular wisdom that earnings management does exist, but is rarely confirmed. Reported earnings in financial statement are subjected to accruals and real earnings management (Enomoto, Kimura, & Yamaguchi, 2015;Francis, Hasan, & Li, 2016;Xu, Taylor, & Dugan, 2007;Hye & Lau 2015). A number of widely discussed models to detect abnormal accruals in earnings management are explained in empirical studies in the 1980s and 1990s (see Beneish, 1999;DeAngelo, 1981;Dechow, Sloan, & Sweeney, 1995;Healy, 1985;J.…”
Section: Accruals and Real Earnings Managementmentioning
confidence: 99%